Measuring net environmental impact from population growth and alternative energy - Travis Edwards (The White Horse Press, 2020)
Existing research on the relationship between economic growth and environmental impact has produced mixed results. Also, there has been a lack of attention on the effect of population, and per capita measures are used rather than total pollution. To address this gap, we analyze the role of population and alternative energy on the environment using total carbon dioxide emissions (CO2) in the United States. We propose a new model integrating population demographics into the Environmental Kuznets Curve, and then apply this framework to an empirical analysis. The effect of population and immigration on total CO2 is estimated, as well as the level of alternative energy use required to overcome increasing environmental pressure. Results suggest population and immigration growth may lead to an increase in total CO2 growth, but alternative energy may lower total CO2 growth after a threshold. Further, immigration and total CO2 growth exhibit a nonlinear relationship.